Using HSV-1 Genome Phylogenetics to Track Past Human Migrations - Kolb, Aaron W.; Ané, Cécile; Brandt, Curtis R. (PLOS ONE, 2013)
We compared 31 complete and nearly complete globally derived HSV-1 genomic sequences using HSV-2 HG52 as an outgroup to investigate their phylogenetic relationships and look for evidence of recombination. The sequences were retrieved from NCBI and were then aligned using Clustal W. The generation of a maximum likelihood tree resulted in a six clade structure that corresponded with the timing and routes of past human migration. The East African derived viruses contained the greatest amount of genetic diversity and formed four of the six clades. The East Asian and European/North American derived viruses formed separate clades. HSV-1 strains E07, E22 and E03 were highly divergent and may each represent an individual clade. Possible recombination was analyzed by partitioning the alignment into 5 kb segments, performing individual phylogenetic analysis on each partition and generating a.phylogenetic network from the results. However most evidence for recombination spread at the base of the tree suggesting that recombination did not significantly disrupt the clade structure. Examination of previous estimates of HSV-1 mutation rates in conjunction with the phylogenetic data presented here, suggests that the substitution rate for HSV-1 is approximately 1.38×10−7 subs/site/year. In conclusion, this study expands the previously described HSV-1 three clade phylogenetic structures to a minimum of six and shows that the clade structure also mirrors global human migrations. Given that HSV-1 has co-evolved with its host, sequencing HSV-1 isolated from various populations could serve as a surrogate biomarker to study human population structure and migration patterns.